Theoretical and experimental investigation into structural and fluid motions at low frequencies in water distribution pipes. (June 2017) - Gao, Yan; Liu, Yuyou
Highlights: Theory of axisymmetric wave propagation at low frequencies is provided. Contributions to the structural and fluid motions are investigated. Two buried pipe systems are presented to support the theoretical findings. Abstract: Vibrational energy is transmitted in buried fluid-filled pipes in a variety of wave types. Axisymmetric ( n  = 0) waves are of practical interest in the application of acoustic techniques for the detection of leaks in underground pipelines. At low frequencies n  = 0 waves propagate longitudinally as fluid-dominated ( s  = 1) and shell-dominated ( s  = 2) waves. Whilst sensors such as hydrophones and accelerometers are commonly used to detect leaks in water distribution pipes, the mechanism governing the structural and fluid motions is not well documented. In this paper, the low-frequency behaviour of the pipe wall and the contained fluid is investigated. For most practical pipework systems, these two waves are strongly coupled; in this circumstance the ratios of the radial pipe wall displacements along with the internal pressures associated with these two wave types are obtained. Numerical examples show the relative insensitivity of the structural and fluid motions to the s  = 2 wave for both metallic and plastic pipes buried in two typical soils. It is also demonstrated that although both acoustic and vibration sensors at the same location provide the identical phase information of the transmitted signals, pressure responses have significantly higher levels than acceleration responses, and thus hydrophones are better suited in a low signal-to-noise ratio (SNR) environment. This is supported by experimental work carried out at a leak detection facility. Additional pressure measurements involved excitation of the fluid and the pipe fitting (hydrant) on a dedicated water pipe. This work demonstrates that the s  = 1 wave is mainly responsible for the structural and fluid motions at low frequencies in water distribution pipes as a result of water leakage and direct pipe excitation.